THE INFLUENCE OF PHONEMIC AWARENESS INSTRUCTION ON EFL EMERGENT READERS’ WORD RECOGNITION - Mohammad Husam Mohammad Alhumsi (Universitas Islam Sumatera Utara (UISU), 2020)
Research has considered phonemic awareness skill as effective pillar in acquiring literacy skills. This skill has been identified as prerequisite for reading success However, little is known about the phonemic awarenessinstruction of Jordanian EFL emergent readers. This study therefore explored the impact of phonemic awareness instruction on word recognition among Jordanian EFL emergent readers.In this study, the research instrument was semi-structured interviews. Seven EFL students of emergent readers were interviewed. They were all first graders aged 7 years on average. Data were analyzed using content analysis. The findings indicated that there is a lack of knowledge or misunderstanding between the term of phonics and phonemic awareness as well. It has been also found that emergent readers’ views show positive support towards the use of phonemic awareness skill. At the end of the study, some pedagogical implications for curriculum designers as well as English teachers were provided accordingly.